Immunomodulation of NK Cells by Ionizing Radiation - Chen, Jiarui; Liu, Xingyu; Zeng, Zihang; Li, Jiali; Luo, Yuan; Sun, Wenjie; Gong, Yan; Zhang, Junhong; Wu, Qiuji; Xie, Conghua (Frontiers in Oncology, 2020)
Natural killer (NK) cells play a critical role in the antitumor immunity. Ionizing radiation (IR) has a pronounced effect on modifying NK cell biology while the molecular mechanisms remain elusive. In this review, we briefly introduce the anti-tumor activity of NK cells and summarize the impact of IR on NK cells both directly and indirectly. On one hand, low-dose ionizing radiation (LDIR) activates NK functions while high-dose ionizing radiation (HDIR) is likely to partially impair NK functions which can be reversed by interleukin (IL)-2 pretreatment. On the other hand, NK functions may be adjusted by other immune cells and the alternated malignant cell immunogenicity under the settings of IR. Various immune cells such as tumor-associated macrophage (TAM), dendritic cell (DC), regulatory T cell (Treg), myeloid-derived suppressor cell (MDSC) and tumor exhibited ligands such as natural killer group 2 member D ligand (NKG2DL), natural cytotoxicity receptors (NCR) ligand, TNF-related apoptosis-inducing ligand-receptor (TRAIL-R), FAS have been involved in this process. By better understanding the molecular basis, it’s promising to augment NK cell-based antitumor immunity in combination with IR.